Selenium Modulates Oxidative Stress-Induced TRPM2 Cation Channel Currents in Transfected Chinese Hamster Ovary Cells - Naziroglu, Mustafa; Ozgul, Cemil; Kucukayaz, Mustafa; Cig, Bilal; Hebeisen, Simon; Bal, Ramazan (Wiley, 2013)
It has been recently reported that the essential antioxidant element selenium has protective effects on cytosolic Ca2+ levels in cell lines. However, the effects of selenium on like transient receptor potential melastatin 2 (TRPM2) in response to oxidative stress (H2O2) are not well understood. We investigated the effects of selenium on H2O2-induced TRPM2 channel currents in the Chinese hamster ovary (CHO) cell line using patch-clamp and fura-2 fluorescence imaging techniques.
Keywords: Hydrogen-Peroxide; Adp-Ribose; Calcium Influx; Quantum Dots; Ca2+ Influx; Activation; Brain; Inhibition; Apoptosis; Toxicity